Effect of high-intensity resistance training on performance of competitive distance runners - Hamilton, R. J.; Paton, C. D.; Hopkins, W. G. (International Journal of Sports Physiology and Performance, 2006)
In a recent study competitive road cyclists experienced substantial gains in sprint and endurance performance when sessions of high-intensity interval training were added to their usual training in the competitive phase of a season. The current study reports the effect of this type of training on performance of 20 distance runners randomized to an experimental or control group for 5 to 7 weeks of training. The experimental group replaced part of their usual competitive-phase training with 10 × 30-minute sessions consisting of 3 sets of explosive single-leg jumps (20 for each leg) alternating with 3 sets of resisted treadmill sprints (5 × ?30-second efforts alternating with 30-second recovery). Before and after the training period all runners completed an incremental treadmill test for assessment of lactate threshold and maximum running speed, 2 treadmill runs to exhaustion for prediction of 800- and 1500-m times, and a 5-km outdoor time trial. Relative to the control group, the mean changes (±90% confidence limits) in the experimental group were: maximum running speed, 1.8% (± 1.1%); lactate-threshold speed, 3.5% (±3.4%); predicted 800-m speed, 3.6% (± 1.8%); predicted 1500-m speed, 3.7% (± 3.0%); and 5-km time-trial speed, 1.2% (± 1.1%). We conclude that high-intensity resistance training in the competitive phase is likely to produce beneficial gains in performance for most distance runners.